2013
DOI: 10.1097/qai.0b013e3182a61ea9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alcohol Consumption and HIV Surrogate Markers in Participants of the Swiss HIV Cohort Study

Abstract: No effect of alcohol consumption on either virological failure or CD4 cell count in both groups of ART-initiating and ART-naive individuals was found. However, severe drinkers were more likely to interrupt ART. Efforts on ART continuation should be especially implemented in individuals reporting high alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 39 publications
4
54
2
1
Order By: Relevance
“…Actually, one of them even proposed that low alcohol consumption can be a predictor of higher CD4+ cell count in HIV-treated patients (Carrieri et al, 2014;Conen et al, 2013). This issue is far from a consensus.…”
Section: Introductionmentioning
confidence: 92%
“…Actually, one of them even proposed that low alcohol consumption can be a predictor of higher CD4+ cell count in HIV-treated patients (Carrieri et al, 2014;Conen et al, 2013). This issue is far from a consensus.…”
Section: Introductionmentioning
confidence: 92%
“…For individuals with liver disease and/or hepatitis C co-infection drinking while taking ART can modify liver drug metabolic rates leading to risk of drug resistance (Kresina et al, 2002). However, with the exception of individuals with compromised liver function, studies suggest that the benefits of sustained adherence to ART on viral suppression and immune system functioning outweigh the negative impacts of mixing alcohol and ART (Conen, et al, 2013; Kowalski, et al, 2012)…”
mentioning
confidence: 99%
“…For example, recent systematic reviews on the association of alcohol and cardiovascular disease outcomes in PLWH [10], and the general population [11] found that nearly every study on the topic relied on an alcohol measurement that was obtained at a single time-point, with most studies using dichotomous categories of “drinkers” and “non-drinkers”. Similar limitations are noted in a recent review of the relationship between alcohol consumption and colorectal cancer in the general population [12], and the relationships between alcohol consumption and HIV-related outcomes such as time to ART initiation and survival [13], and rate of CD4 decline over time [8]. …”
Section: Key Issues In Analytic Strategymentioning
confidence: 64%
“…Because alcohol consumption varies over time, measurement of this exposure is complex. Alcohol consumption is highly prevalent among PLWH [8] and has been associated with biological and behavioral influences on health outcomes related to HIV/AIDS [9]. …”
Section: Introductionmentioning
confidence: 99%